Conceptualising psycho-emotional aspects of disablist discrimination and impairment : towards a psychoanalytically informed disability studies - Watermeyer, Brian Paul (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Psychology))—University of Stellenbosch, 2009.